ESTABLISHMENT OF ENTREPRENEURIAL ACTIVITIES TO STUDENTS, RURAL YOUTH AND EMPOWERING WOMAN TO CREATE ENTREPRENEURISM AND EMPLOYMENT GENERATION WITH SPECIAL REFERENCE TO EDUCATIONAL INSTITUTIONS - Dr.K.V.V.RAJU, Dr. B. Kishore Babu, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
All the colleges engineering PG Degree colleges in Andhra Pradesh Performing well in organizing academic classes and programs. It is observed that students IQ is improving and developing. Now it is the right time to put them in right path. The whole world is in changing scenario. The production of graduates and post graduates tremendously increasing. It is becomes very difficult for the governments and colleges to provide employment. The modern objective of education is getting placement or employment. It is the right time to think for a solution or searching alternative methods to create income generation.2